Oxo-M and 4-PPBP Delivery via Multi-Domain Peptide Hydrogel Toward Tendon Regeneration - Park, Ga Young; Tarafder, Solaiman; Eyen, Samantha Lewis; Park, Soomin; Kim, Ryunhyung; Siddiqui, Zain; Kumar, Vivek; Lee, Chang H. (Frontiers in Bioengineering and Biotechnology, 2022)
We have recently identified novel small molecules, Oxo-M and 4-PPBP, which specifically stimulate endogenous tendon stem/progenitor cells (TSCs), leading to potential regenerative healing of fully-transected tendons. Here we investigated an injectable, multidomain peptide (MDP) hydrogel providing controlled delivery of the small molecules for regenerative tendon healing. We investigated the release kinetics of Oxo-M and 4-PPBP from MDP hydrogels and the effect of MDP-released small molecules on tenogenic differentiation of TSCs and in vivo tendon healing. In vitro, MDP showed a sustained release of Oxo-M and 4-PPBP and a slower degradation than fibrin. In addition, tenogenic gene expression was significantly increased in TSC with MDP-released Oxo-M and 4-PPBP as compared to the fibrin-released. In vivo, MDP releasing Oxo-M and 4-PPBP significantly improved tendon healing, likely associated with prolonged effects of Oxo-M and 4-PPBP on suppression of M1 macrophages and promotion of M2 macrophages. Comprehensive analyses including histomorphology, digital image processing, and modulus mapping with nanoindentation consistently suggested that Oxo-M and 4-PPBP delivered via MDP further improved tendon healing as compared to fibrin-based delivery. In conclusion, MDP delivered with Oxo-M and 4-PPBP may serve as an efficient regenerative therapeutic for in situ tendon regeneration and healing.